Exploring the self-reported knowledge and value of implementation of content and language objectives of high school content-area teachers - Kim, Seong-Shin (Kansas State University, 2007)
Four high schools with high ELL enrollment and a high percentage of teachers taking graduate-level ESL courses participated in this quantitative study. The content-area teachers completed a Survey of Teachers’ Knowledge and Value of Implementation of Content and Language Objectives. The survey included two sections: (a) a demographics section and (b) a support section in which respondents self-rated their knowledge and value on content and language objectives. Descriptive statistics were used to generate the mean, standard deviation, and frequency distribution of the demographics of the samples, which were independent variables of this study. Inferential statistics on the research hypotheses were calculated using multiple correlation/regression and one-way ANOVA. Results from the support section indicated respondents perceived their knowledge and value on content and language objectives were not lacking. However, results also revealed that teachers rated themselves lower on knowledge and value on implementing language objectives than they did on knowledge and value on implementing content objectives. In addition, data analysis revealed that percentage of students who were ELL last year and hours of ESL related training can be linked to the teachers’ self-rated degree of knowledge and value on implementing content and language objectives. As a result of this study, five recommendations for practice were made. Of these, the researcher believes the following to be most crucial: (1) Because the number of ELL students continues to increase, even those teachers who currently have a small number of ELL students in their classrooms must be willing to enhance their knowledge and value on content and language objectives; (2) Teacher educators for pre-service programs should place greater emphasis on the integration and implementation of content and language objectives; and (3) Staff developers should be informed of a need to increase the professional development of in-service teachers with regard to language objectives. Among other recommendations for future research, the researcher suggests the need for future studies to include more specific investigations on how teachers construct language objectives. Furthermore, future studies should pursue ways to encourage educators to participate in ESL related workshops or trainings and to form mentoring relationships with colleagues.
Keywords: Language objectives; Content objectives; ESL; ELL; ICB; Sheltered instruction; Education, Secondary (0533)